Youtube para o ensino de história: tutorial para a seleção e utilização de audiovisuais - Helfer, Arioli Domingos dos Reis (2021)
Before the discussions about internet’s advance as an educational tool, more precisely the influence of historical content producers in the world wide web, the aim of this study is to recognize YouTube as a didactic resource for history teaching. By applying a survey to the basic educational network teachers, I verified the teachers’ opinions about the usage of YouTube as a didactic resource, and their understandings about continuous development. The participant teachers approve the use of videos from the platform because of its easy access, attractivity and help in learning, demonstrating interest in understanding how to use such resource in the classroom. Concerning continuous development, teachers consider it as an experience exchanging, qualification, reassessment of their knowledge, updating and adding moment. Moreover, they emphasize the need of a dynamic moment, held by capable people, with classroom experience and who care about teaching-learning processes. The scholar uses of videos produced for the internet was advised by public history perspectives, with the creation of criteria for the selection of videos from the YouTube platform that are committed to scientific disclosure. The reflections of public history practices worked as a guide in the search for converging content produced for informal disclosure with the formal school context, in favor of educational work. Based on the study results, I present a proposal of continuous development focused on qualifying the criteria in the search and selection of YouTube videos for usage in history classes of teachers from basic education.